The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1128/jmbe.v10.96
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Interrupted Case Studies to Enhance Critical Thinking Skills in Biology

Abstract: There has been a dramatic increase in the availability of case studies for use in the biology classroom, and perceptions of the effectiveness of case-study-based learning are overwhelmingly positive. Here we report the results of a study in which we evaluated the ability of interrupted case studies to improve critical thinking in the context of experimental design and the conventions of data interpretation. Students were assessed using further case studies designed to evaluate their ability to recognize and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 6 publications
1
14
0
4
Order By: Relevance
“…Cases create the need to know, enhancing the listening and cooperative learning skills of the students, building partnerships among learners and teachers, encouraging attention to and self-consciousness toward assumptions and conceptions, help students learn to monitor their own thinking, and promote thinking and brainstorming (Grupe & Jay, 2000). White et al (2009) stated that case studies have wide value in classrooms. In addition, in their study, they also showed a major increase in the number of students who critically analyzed and evaluated in thinking demonstrated that there is a statistically significant increase in the number of students capable of critical analysis and evaluation in thinking.…”
Section: Case Study Methods and Critical Thinking Skillsmentioning
confidence: 99%
“…Cases create the need to know, enhancing the listening and cooperative learning skills of the students, building partnerships among learners and teachers, encouraging attention to and self-consciousness toward assumptions and conceptions, help students learn to monitor their own thinking, and promote thinking and brainstorming (Grupe & Jay, 2000). White et al (2009) stated that case studies have wide value in classrooms. In addition, in their study, they also showed a major increase in the number of students who critically analyzed and evaluated in thinking demonstrated that there is a statistically significant increase in the number of students capable of critical analysis and evaluation in thinking.…”
Section: Case Study Methods and Critical Thinking Skillsmentioning
confidence: 99%
“…The case studies were developed based on examples provided by Prof. Revati Masilamani at a SALTISE conference. The examples brought by Prof. Masilamani were tailored for natural scientists/biologists [2]. For MIME 317, we developed cases studies tailored to Materials Engineers.…”
Section: Case Study Developmentmentioning
confidence: 99%
“…The interrupted case studies method uses case studies taken from real-world problems, and breaks them down in smaller pieces; the students work on the smaller parts in teams during the lecture, and get feedback from the professor before moving on to the next part of the case [1]. This approach has been used in natural sciences [2] but this was the first attempt in an Engineering setup.…”
Section: Introductionmentioning
confidence: 99%
“…Varela et al, 2005;. Berpikir kritis merupakan sebuah proses penilaian self-regulatory yang bertujuan untuk mendorong pemecahan masalah dan pengambilan keputusan, atau "mesin" yang mendorong bagaimana kita memutuskan apa yang harus dilakukan atau percaya pada konteks tertentu (Qiutadamo et al, 2008;White & Whitaker, 2009;Tan, 2004) dan dapat berupa aktivitas mental . Menurut berpikir kritis harus selalu mengacu dan berdasar kepada suatu standar yang disebut standar universal intelektual.…”
Section: Metodologiunclassified